Strengthening foundational literacy : a process and outcome evaluation of the Wordworks Early Literacy programme - Okeyo, Alicia (Institute for Monitoring and Evaluation, 2016)
The purpose of this evaluation was to investigate the effects of a volunteer-run, school-based Wordworks Early Literacy intervention that was implemented in the Western Cape for struggling Grade One learners at risk of falling into the Learning Achievement Gap. The process evaluation investigated the extent to which volunteers received adequate training to deliver the programme to learners, as well as the perceived benefits that volunteers gained from this experience. The outcome evaluation investigated the extent to which several literacy and psychosocial development indicators improved amongst children who took part in The Wordworks Early Literacy Programme (ELP). Secondary data from volunteer programme records such as attendance of training sessions, volunteers' reasons for leaving the programme where applicable, and a Volunteer Feedback survey detailing perceived benefits of volunteering, were analysed to ascertain the volunteer outcomes. Secondly, data from learner assessments measuring changes in literacy indicator variables (such as letter knowledge, sentence construction ability, and reading ability), in 3 cohorts of learners enrolled in the programme, were analysed. Cohort 1 consisted of the 2014 12-month programme, Cohort 2 of the 2014 6-month programme and Cohort 3 of the 2015 6-month programme. Thirdly, qualitative data from responses given in a Teachers Feedback survey, detailing perceived changes in learner psychosocial well-being, were analysed.